Dopamine Neurons in the Ventral Tegmental Area: An Autopsy Case of Disorganized Type of Schizophrenia - Keiko Ikemoto; Tatsuro Oda; Akiyoshi Nishimura; Katsuji Nishi (Case Reports in Neurological Medicine)
The mesolimbic dopamine (DA) system has been associated with the pathogenesis of schizophrenia. Here, we examined DA-containing neuronal structures of the ventral tegmental area (VTA) of an autopsy case of disorganized type of schizophrenia (75-year-old female), using tyrosine hydroxylase (TH) immunohistochemistry. A free floating method using 50-μm cryostat sections and three-dimensional imaging analyzer AxioVision were applied to observe the wide range structures of TH-immunoreactive (-ir) neurons. TH-ir neuronal cell bodies in the VTA of the present case had irregular shape and various size, and TH-ir neuronal processes had irregular thickness and straightened shape or curved shape having many corners, when compared to a control autopsy case with no detectable neurological and psychiatric diseases (64-year-old male). The mechanisms underlying the morphological characteristics of DA neurons of the brains with schizophrenia should be elucidated epigenetically as well as genetically.